HIGHER EDUCATION STUDENTS’ EXPERIENCE IN A DIGITAL EDUCATIONAL MODALITY (Proceedings of the International Conference on Education, 2021)
In 2020, universities worldwide migrated abruptly from face-to-face education to an emergency remote distance format to respond to the SARS-CoV-2 pandemic. The present study aimed to assess this type of learning experience from higher education students' perspectives. A mixed-method design was conducted with 796 students from six different disciplinary schools. The questionnaire included five constructs (Pedagogical, Collaboration, Learning Resources, Time Management, and Functional Features) with 17 quantitative items rated on a 1-5 Likert scale (Cronbach's Alpha = 0.955). Answers from two open questions were coded into two categories: Positive Experiences and Aspects to Improve. The highest constructs were Functional Features (3.60) and Time Management (3.15). The lowest score was Collaboration (2.77). Students appreciated the digital experience using Zoom and Canvas and their flexibility with time and space in their self-management. They recommended improving the interactions among peers and teachers with shorter and more interactive synchronous sessions. Even though there was only one week to prepare for the change from face-to-face to emergency remote distance learning, the students successfully continued their education. An updated distance teaching method was improved and implemented after reviewing the results of the present study. Since August 2020, more than 50 thousand higher education students have been taught via this enhanced digital educational modality.
Keywords: Educational Innovation; Higher Education; digital education; flexible education; Zoom; Canvas; SARS-CoV-2